Ultrasound‐guided injection of the median artery in the standing sedated horse. (20th April 2014) - Spriet, M.; Trela, J. M.; Galuppo, L. D.
Summary Reasons for performing study Injection of the median artery of horses leads to better distribution and persistence of mesenchymal stem cells than i.v. regional limb perfusion. Due to technical difficulties, intra‐arterial injections thus far have only been performed under general anaesthesia. Objectives To assess the feasibility of injection of the median artery in standing sedated horses. Study design Experimental study. Methods Six horses were included in the study. After median and ulnar regional analgesia, radiographic contrast material was injected in the median artery of both front limbs, using a catheter in one limb and a direct needle injection in the other. Ultrasound guidance was used for catheter and needle placement. Radiographs were obtained for confirmation of successful injection. Post procedural ultrasound examination was performed to assess vascular compromise. Results Catheter placement was successful in all 6 limbs, but in one limb injection was not possible due to arterial spasm. Movement of the limbs after the initial injection resulted in loss of functionality of the catheter in 2 other horses. Direct needle injection was successful on all 6 limbs, with periarterial extravasation observed in 2 limbs. No clinical complications were observed. Conclusions Injection of the median artery can be performed in standing horses under sedation. Direct needle injection is a more practical technique than catheterisation, as it is easier to perform and less likely to induce arterial spasm. Periarterial extravasation remains a possible limitation of the technique. Intra‐arterial injections may be useful for administration of therapeutic agents such as mesenchymal stem cells on standing sedated horses.